رِاظةى رِةنطدانةوةى بةهايي نيَوان ئايني و سياسةت خويَندنةوةيةكى تيؤرى بؤ كؤمةلَطةيةكى سياسى تةواوكار - ث.ي.د. سةردار قادر حمى الدين (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The importance of research in issues that revolve around the nature of value the relationship between religion and political by nature reflectiveness between values and political behavior, and there are attempts by a variety of different aspects of in order to find a compromise between the two phenomena, but the thought exclusionary prevailing between the two currents did not lead to a satisfactory result limit now, even the community in a state of unremitting Ranging internal fragmentation and to wrestle at the level of values. This project is an attempt to find a compromise as a result of the conflict historical prevailing over a century ago, has not decided yet, but there are mounting and the renewal of the conflict from time to time and again. So not a modern relationship between religion and the state a new order, but the project focuses on how and what the exploitation of religion and revealed its position in the political life of the community, this issue is extremely important to the project and directs the student in this way in order to find a compromise solution to get out of that dilemma suffered by communities developing and missed her progress and development, social cohesion, and eventually led to the tireless struggle between the spectra of power and identity. Research Hypothesis also lies in: that each political behavior of the ad valorem system behind it, and cannot grow or develop only through them. Even leading up to the value system of political behavior and not vice versa. A reflexive relationship between values and politics in general, as there reflectivity between religion and politics relationship, but the relationship between religion and state is different from the first embodiment cannot be religion in the state and that the power control and from which its name.